Cross-presentation of Listeria monocytogenes-derived CD4 T cell epitopes - Škoberne, Mojca; Schenk, Simone; Hof, Herbert; Geginat, Gernot (The journal of immunology, 2002)
Listeriolysin O (LLO) mediates the evasion of Listeria monocytogenes from the phagolysosome into the cytoplasm of the host cell. The recognition of infected cells by CD4 T cells is thought to be limited by the evasion of bacteria from the phagolysosome and also by the direct LLO-mediated inhibition of CD4 T cell activation. To analyze the influence of these immunoevasive mechanisms on the antilisterial CD4 T cell response, the expansion of L. monocytogenes-specific CD4 and CD8 T cells was monitored in infected mice. It was found that expansion of L. monocytogenes-specific CD4 T cells occurred synchronously with CD8 T cell expansion. The analysis of Ag presentation by macrophages and dendritic cells isolated from spleens of infected mice revealed efficient presentation of L. monocytogenes-derived CD4 T cell epitopes that was not dependent on the actA-mediated intercellular spread of bacteria. The further in vitro Ag presentation analysis revealed that although L. monocytogenes-infected macrophages and dendritic cells were poor presenters of CD4 T cell epitopes, more efficient presentation occurred after cocultivation of noninfected dendritic cells or macrophages with infected cells. These data indicate that the suppressive effect of LLO on the antilisterial CD4 T cell response is maintained only in infected APC and support the hypothesis that cross-priming plays a role in the induction of the strong CD4 T cell response in Listeria-infected mice.
Gesehen am 07.04.2022